Chronic benzodiazepine treatment triggers gephyrin scaffold destabilization and GABAAR subsynaptic reorganization - Chapman, Caitlyn A.; Povysheva, Nadya; Tarr, Tyler B.; Nuwer, Jessica L.; Meriney, Stephen D.; Johnson, Jon W.; Jacob, Tija C. (Frontiers in Cellular Neuroscience, 2025)
Benzodiazepines (BZDs) are important clinical drugs with anxiolytic, anticonvulsant, and sedative effects mediated by potentiation of inhibitory GABA type A receptors (GABAARs). Tolerance limits the clinical utility of BZDs, yet the mechanisms underlying tolerance after chronic exposure have not been thoroughly investigated. Here, we assessed the impact of chronic (7-day) treatment with the BZD diazepam (DZP) on the dynamic plasticity and subsynaptic organization of the gephyrin scaffold and γ2 subunit-containing GABAARs in primary neurons. After functional confirmation of diminished BZD sensitivity, we provide the first super-resolution analysis of inhibitory nanoscale plasticity induced by chronic BZD exposure: gephyrin subsynaptic domains were smaller and the inhibitory postsynaptic area was overall diminished by DZP treatment, resulting in a condensation of synaptic γ2-GABAARs into smaller synaptic areas. Using a novel fluorescence-based in situ proximity ligation assay and biochemical fractionation analysis, the mechanism for gephyrin downregulation was revealed to be dependent on phosphorylation and protease cleavage. Accordingly, DZP treatment impaired gephyrin synaptic stability, demonstrated by live-imaging photobleaching experiments. Despite the loss of BZD sensitivity and stable synaptic gephyrin, 7-day DZP treatment did not reduce the surface or total protein levels of BZD-sensitive γ2-GABAARs, as shown in prior short-term BZD treatment studies. Instead, chronic DZP treatment induced an accumulation of γ2-GABAARs in the extrasynaptic membrane. Surprisingly, γ2-GABAAR interactions with gephyrin were also enriched extrasynaptically. An identified rise in extrasynaptically-localized gephyrin cleavage fragments may function to confine receptors away from the synapse, as supported by a decrease in extrasynaptic γ2-GABAAR mobility. Altogether, we find that chronic BZD treatment triggers several subtle converging plasticity events at inhibitory synapses which effectively restrict the synaptic renewal of BZD-sensitive GABAARs via mechanisms distinct from those observed with short-term treatment.